Microstructural optimization and functional enhancement of Ag-Si and Ag-Si-SiC nanocomposite coatings: a comparative study with Ag-Ge coatings - Faranak Bakhtiarifard; Nasim Nayebpashaee (Discover Materials)
Abstract This work explores the creation of silver-silicon (Ag-Si) and silver-silicon-silicon carbide (Ag-Si-SiC) nanocomposite ceramic coatings as cost-effective alternatives to silver-germanium (Ag-Ge) coatings for industrial applications. The coatings were fabricated via pulse-reverse electroplating, utilizing silicon (Si) and silicon carbide (SiC) nanoparticles to optimize microstructure and enhance functional properties. Incorporation of 4 g/L SiC nanoparticles enhanced wear resistance and mechanical durability, whereas 1 g/L silicon dioxide improved corrosion resistance. Microstructural analysis using Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) revealed that Ag-Si-SiC coatings possess a dense, homogeneous morphology, contributing to reduced surface roughness and enhanced mechanical integrity. Electrochemical corrosion tests in ammonium sulfide solution demonstrated that SiC nanoparticle incorporation significantly enhanced coating durability in aggressive environments, reducing corrosion current density from 1.2 ± 0.08 × 10⁻⁵ A/cm² (Ag-Si) to 1.01 ± 0.07 × 10⁻⁵ A/cm² (Ag-Si-SiC). Wear tests further highlighted the role of SiC reinforcement in tribological performance, showing a decrease in the coefficient of friction (COF) from 0.52 ± 0.03 to 0.39 ± 0.02. The ceramic-based nanocomposite structure of Ag-Si-SiC coatings enhances mechanical robustness and wear resistance, positioning them a competitive alternative for industrial use, despite Ag-Ge coatings exhibiting slightly superior corrosion resistance. Furthermore, the affordability and abundance of silicon-based materials support their scalability for large-scale applications in advanced ceramic engineering.